PERCEIVED ORGANIZATIONAL SUPPORT, WORK-FAMILY CONFLICT, AND JOB SATISFACTION: A SERIAL MEDIATION MODEL - Muzakki Muzakki; Asep Heryyanto (Media Mahardhika, 2022)
This study aims to examine the influence of perceived organizational support on work-family conflict and job satisfaction, and the influence of work-family conflict on job satisfaction. This study also aims to examine the role of work-family conflict mediation in the relationship between perceived organizational support and job satisfaction. The method used is quantitative, and the sample technique used is random sampling using the distribution of questionnaires to collect data from the research object. The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS). Furthermore, the findings of this study reveal that percieved organizational support has a positive and significant effect on job satisfaction. Percieved organizational support also negatively affects work-family conflict. Meanwhile, work-family conflict has a positive and significant effect on job satisfaction. The latest finding is work-family conflict is able to negatively mediate the relationship of percieved organizational support to job satisfaction.